2009
DOI: 10.1175/2009mwr2672.1
|View full text |Cite
|
Sign up to set email alerts
|

Multimodel Ensemble ENSO Prediction with CCSM and CFS

Abstract: Results are described from a large sample of coupled ocean-atmosphere retrospective forecasts during 1982-98. The prediction system is based on the National Center for Atmospheric Research (NCAR) Community Climate System Model, version 3 (CCSM3.0), and a state-of-the-art ocean data assimilation system made available by the National Oceanic and Atmospheric Administration (NOAA) Geophysical Fluid Dynamics Laboratory (GFDL). The retrospective forecasts are initialized in January, April, July, and November of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 128 publications
(77 citation statements)
references
References 57 publications
3
73
1
Order By: Relevance
“…This sensitivity is associated with the uncertainty in subgrid scale parameterized physics and model numerics. The recognition of the importance of this sensitivity has led to a number of efforts that have demonstrated that a multi-model ensemble strategy is the best current approach for adequately resolving forecast uncertainty and the forecast probability distribution in seasonal-tointerannual predictions ( [65], [66], [67], [68], [69]). Another recently proposed methodology is to use stochastic-dynamic parameterization techniques which perturb parameterizations in such a way as to improve on the benefits of a multi-model ensemble by using a single model [70].…”
Section: Figure 5 Observed and Hindcast Ten Year Mean (Top) Global Smentioning
confidence: 99%
“…This sensitivity is associated with the uncertainty in subgrid scale parameterized physics and model numerics. The recognition of the importance of this sensitivity has led to a number of efforts that have demonstrated that a multi-model ensemble strategy is the best current approach for adequately resolving forecast uncertainty and the forecast probability distribution in seasonal-tointerannual predictions ( [65], [66], [67], [68], [69]). Another recently proposed methodology is to use stochastic-dynamic parameterization techniques which perturb parameterizations in such a way as to improve on the benefits of a multi-model ensemble by using a single model [70].…”
Section: Figure 5 Observed and Hindcast Ten Year Mean (Top) Global Smentioning
confidence: 99%
“…The NMME is based on the recognition that multimodel ensemble approaches generate better forecasts than any single model ensemble (e.g., Doblas-Reyes et al, 2005, Kirtman and Min, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The fundamental question regarding the predictability limits of the coupled ocean-atmosphere system has not been well established yet, although recent coupled models are able to forecast phenomena like El Niño-Southern Oscillation (ENSO) up to about one year in advance (Kirtman and Min, 2009). The atmospheric predictability has been extensively investigated in the past, and classical predictability studies (Lorenz, 1965(Lorenz, , 1969Charney et al, 1966;Smagorinsky, 1969;Shukla, 1985) have established that the instantaneous state of the atmosphere cannot be predicted beyond a few weeks.…”
Section: Introductionmentioning
confidence: 99%